Analysis of the Determinants of Agricultural Investment Decisions in Burkina Faso - Adiaratou Diallo; Pam Zahonogo (Research in Applied Economics, 2024)
Agricultural investment contributes to increased productivity and production. This research analyzes the determinants of agricultural investment decisions in Burkina Faso. A double hurdle model is used to analyze the factors that explain agricultural investment and intensification decisions based on data collected in 2017 by the Laboratory of Quantitative Analysis of Development in Sahel (LAQAD-S). The results show that off-farm income and level of education positively affect household agricultural investment. Economic policy measures to develop income-generating activities and improve household education levels are crucial to raising the level of agricultural investment by rural households in Burkina Faso.